Pain Management in the Context of a Nursing Help Line: Identification of Needs, Development of a Continuing Education Activity, and Evaluation of its Impact - Boisvert, Marc; Bilodeau, Charles; Bourgault, Patricia; Gallagher, Frances (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2019)
Introduction: Pain management by nurses in the context of a phone help line is a complex task. Continuing education (CE) is a potentially effective strategy to ensure development of this competence. Objective: The main objective of this study was to develop and evaluate a customized pain management CE activity by and for nurses working at a phone help line providing health information. Methods: A three-phase convergent mixed-method design was used: needs and preferred educational strategies assessment, conception of CE activity, evaluation. Based on a participatory approach, the CE activity was developed to meet participants’ expectations and needs. It included two components: 1) CE day and 2) individual clinical support. A quasi-experimental study with a single time series was used to evaluate the CE activity regarding participants’ knowledge and beliefs about pain management and their perceptions of their pain management activities. Data collection was performed using focus groups and questionnaires. Results: Participants’ knowledge about pain management increased after the CE day and remained stable after three months. Also, participants reported an increase in various patient-centered pain management nursing activities. Discussion and conclusion: This study illustrates the importance of involving nurses in designing a CE activity and supports its potential benefits in the context of a phone help line.